Ancient political thought and Leo Strauss in the mirror of modern Chinese (mis)interpretations. Bartsch, S. (2023). Plato Goes to China: the Greek Classics and Chinese Nationalism. Princeton: Princeton UP. - Zalozetskyi, Vitalii (Sententiae, 2025)
Review of Bartsch, S. (2023). Plato Goes to China: the Greek Classics and Chinese Nationalism. Princeton: Princeton UP.